Seminal characteristics of genetically improved farmed Tilapia (GIFT) strain induced with different doses of spawning agent - Abdul Aziz, Nur Syafiqah (2016)
Genetically Improved Farm Tilapia (GIFT) strain was developed through selective breeding of Nile tilapia and was cultured worldwide due to its ability to tolerate wide range of water conditions. There were limited studies on the effects of spawning agent (to induce maturation and increase milt production) on seminal characteristics of GIFT strain. This study was carried out to determine the effects of different doses of a spawning agent (Ovaprim®) on seminal characteristics of GIFT strain as well as to determine the optimum dose of the spawning agent. There were four treatment groups which consisted of 0 (control), 0.1, 0.3 and 0.5ml/kg and the body weight was between the range of 200 to 360 grams. The fish was injected intramuscularly and the milt was collected after 12 hours (latency period) through gentle abdominal pressure. The volume of milt was recorded and sperm parameters such as sperm density, motility, viability and morphometry were evaluated. There was significant difference for sperm motility but other parameters were not significance. Treatment group 0.5 ml/kg has the highest mean for sperm density, motility and viability, which made it as the optimum dose for Ovaprim®. Thus, these parameters are usually being used to determine the sperm quantity and quality.